2013
DOI: 10.1111/cmi.12212
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration and histopathology in P lasmodium chabaudi malaria are influenced by the immune response in an organ‐specific manner

Abstract: Infection with the malaria parasite, Plasmodium, is associated with a strong inflammatory response and parasite cytoadhesion (sequestration) in several organs. Here, we have carried out a systematic study of sequestration and histopathology during infection of C57Bl/6 mice with Plasmodium chabaudi AS and determined the influence of the immune response. This parasite sequesters predominantly in liver and lung, but not in the brain, kidney or gut. Histopathological changes occur in multiple organs during the acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(120 citation statements)
references
References 50 publications
(94 reference statements)
9
106
1
4
Order By: Relevance
“…Also blood leukocytes infiltrate the liver and produce inflammatory mediators thereby enhancing hepatic inflammation. A recent paper by Brugat et al confirmed the inflammatory etiology of liver pathology in Pc AS-infected C57BL/6 mice, as they found that the increase of serum ALT levels is abrogated in rag −/− and IFN-γ receptor −/− mice [23]. Furthermore, the liver also has an important role in the induction of immune tolerance and it produces high amounts of anti-inflammatory molecules.…”
Section: Discussionmentioning
confidence: 88%
“…Also blood leukocytes infiltrate the liver and produce inflammatory mediators thereby enhancing hepatic inflammation. A recent paper by Brugat et al confirmed the inflammatory etiology of liver pathology in Pc AS-infected C57BL/6 mice, as they found that the increase of serum ALT levels is abrogated in rag −/− and IFN-γ receptor −/− mice [23]. Furthermore, the liver also has an important role in the induction of immune tolerance and it produces high amounts of anti-inflammatory molecules.…”
Section: Discussionmentioning
confidence: 88%
“…34,35 Liver damage has also been observed in mice infected with P. yoelii 17XNL, Plasmodium chabaudi, and Plasmodium berghei. [36][37][38] In particular, apoptosis of hepatocytes has been shown to be induced by infection-associated oxidative stress and liver metabolic dysfunction can result from immunopathology during malaria. 39,40 The spleen is crucial to clearance of Plasmodiuminfected RBCs.…”
Section: Resultsmentioning
confidence: 99%
“…Liver is one of organs in which iRBCs preferentially accumulate to avoid immune system surveillance inside the spleen, and iRBC sequestration within the liver endothelium is now emerging as another factor that promotes liver damage [40][41][42]. Several studies suggest that iRBC sequestration contributes to the intrahepatic obstruction of blood flow, which leads to hepatocellular hypoxia and excessive intravascular hemolysis, causing increased oxidative stress and leukocyte infiltration [40,[43][44][45]. Infiltrated leukocytes also produce inflammatory mediators, thereby enhancing hepatic inflammation [43,46].…”
Section: Discussionmentioning
confidence: 99%